Ethnic disparities in the graduate labour market - Aslan Zorlu (Institute for the Study of Labor (IZA), 2011)
This paper examines ethnic wage differentials for the entire population of students enrolled in 1996 using unique administrative panel data for the period 1996 to 2005 from the Dutch tertiary education system. The study decomposes wage differentials into two components: a component which can be explained by the observed characteristics and unexplained component. The analysis provides novel evidence for the magnitude and the origin of ethnic wage differentials by gender. In general, ethnic wage gap is larger for migrant women than migrant men and larger for Western and Caribbean migrants than Mediterranean migrants. Ethnic minority students appear to have large wage surplus which is almost entirely explained from their favourable observed characteristics. Most notably, Mediterranean female graduates have significant positive wage discrimination while Western female graduates seem to face a small wage penalty.
urn:nbn:de:101:1-2012010913793
Keywords: J15; J24; J31; 330; college; university; wages; qualifications; dropout; Lohndifferenzierung; Ethnische Gruppe; Studierende; Absolventen; Geschlecht; Niederlande